Model Problem Based Learning dengan Metode Case Study pada Materi Perubahan Lingkungan untuk Meningkatkan Sikap Sadar Lingkungan pada Peserta Didik Kelas X3 SMAN 18 Surabaya - Putra, Bima Purnama; Pertiwiningrum, Agustina; Kasminah (Undiksha, 2023)
Based on interviews and observations conducted at SMAN 18 Surabaya, show the fact that environmental awareness from students X3 SMAN 18 Surabaya needs to be improved. The purpose of this research was to increase the environmental awareness of students from class X3 SMAN 18 Surabaya by applying a problem-based learning model with a case study method on environmental change topics. This research was conducted using collaborative classroom action research with 2 cycles, each cycle had four phases which were planning, action, observation, and reflection. This research was conducted in SMAN 18 Surabaya and Jangkar Park Jambangan, with 33 students from X3 as the subject of this research. The data from this research were collected using observation sheets and survey sheets. Then the data was analyzed using quantitative descriptive methods. The results showed that the problem-based learning model and case study method can be used to increase student's environmental awareness, it can be proven by looking at class X3 environmental awareness form observation sheet that increased from 62,33% at cycle 1 and became 80% at cycle 2, then it also can be proved by look at the data from survey sheet that also has increased from just 67% students that can be categorized have good environmental awareness at cycle 1 became 100% students that can be categorized have good environmental awareness at cycle 2. Based on the research it can be concluded that a problem-based learning model with a case study method on environmental change topics can be used to increase students' environmental awareness.